Valorising the IoT Databox: creating value for everyone. Issue 1 (11th November 2016) - Perera, Charith; Wakenshaw, Susan Y. L.; Baarslag, Tim; Haddadi, Hamed; Bandara, Arosha K.; Mortier, Richard; Crabtree, Andy; Ng, Irene C. L.; McAuley, Derek; Crowcroft, Jon
Abstract: The Internet of Things is expected to generate large amounts of heterogeneous data from diverse sources including physical sensors, user devices and social media platforms. Over the last few years, significant attention has been focused on personal data, particularly data generated by smart wearable and smart home devices. Making personal data available for access and trade is expected to become a part of the data‐driven digital economy. In this position paper, we review the research challenges in building personal Databoxes that hold personal data and enable data access by other parties and potentially thus sharing of data with other parties. These Databoxes are expected to become a core part of future data marketplaces. Copyright © 2016 The Authors Transactions on Emerging Telecommunications Technologies Published by John Wiley & Sons, Ltd. Abstract : Over the last few years, significant attention has been focused on personal data. Making personal data available for access and trade is expected to become a part of the data‐driven digital economy. In this paper, we review the research challenges in building personal Databoxes that hold personal data and enable data access by other parties and potentially thus sharing of data with other parties. These Databoxes are expected to become a core part of future data marketplaces.